TEACHING STRATEGIES FOR IMPROVING LANGUAGE ASSESSMENT - Namozova Nargiza (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract. This master’s dissertation is devoted to the problem of assessing language skills. It introduces the purposes and basic types of assessment, provide some guidelines for testing large, multilevel classes, and provide suggestions for evaluating listening, speaking, reading, and writing in large multilevel classes.